RESEARCH INFRASTRUCTURE OF BRICS COUNTRIES - ILYA GEORGIEVICH Korotkov; VERA ANDREEVNA Zubenko (Мир новой экономики, 2018)
The research infrastructure mega-science projects are the driving force of the science and technological development. BRICS countries take a part in the realization of various major international projects. Creating of suchprojects is a result of team work, of concentration of financial and intellectual resources of several countries, forexample - the projects of the Large Hadron Collider and ITER. Russia announced an initiative to create a globalsystem of research infrastructure GRAIN (Global Research Advanced Infrastructure Network) to provide all BRICS countries with access to the mega-science projects infrastructure. The realization of these programs will enablenot to duplicate the same projects on the same territory, will provide more efficient resource utilization orientedto the development of science research infrastructure. It will enable to exchange the ideas, will accelerate the development of science and technologies in BRICS countries. The efficiency of the new structure depends on theright system of management which will determinate the development of BRICS countries and the openness of GRAIN to the rest of the world. The most highly developed European network is a base, an example and general partner for BRICS countries. Today it is not necessary to claim for being the main centre. The creation of several competing centers which complete each other - is a unique opportunity of development and of a new step in the interests not only of BRICS countries but also of the whole world.